PENGARUH HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PENGGUNAAN KERETA API FAJAR UTAMA SEMARANG RELASI SEMARANG – JAKARTA - Pandu Wijanarko; Apriatni Endang Prihatini; Widayanto Widayanto (Jurnal Ilmu Administrasi Bisnis, 2015)
Price will be considered a person before buying anything. Especially in service’s field, quality of service will be an additional consideration for a person berfore determining a choice of services. PT Kereta Api Indonesia (persero) will certainly pay attention to these two aspects in order to be a leader of mass land transport and become people’s choice while many private vehicles increasingly then causing traffic jams on the road. The purpose of this study to determine the effect of price anda quality service to the usage-decision of Fajar Utama Semarang train. This research method is an Explanatory with data collection through interviews, questionnaires anda literature study. Accidental and purposive samplings technique is used with a sample of 100 people. Anlysis technique used was qualitative and quantitative using validity, reliability test, correlation coefficient, simple and multiple regression analysis, the coefficient determination, cross-tab, and significance test (t test and F test).Conclusion the study shows the price and service quality simultaneously influence the usage-decision of the passenger. This proved by the corellation coefficient score at 55,7% which in the strong category. Even so the determination coefficient score only at 31%. A good idea to PT Kereta Api Indonesia (persero) should pay attention to the price comparison with competitors. If the quality are not spesifically different, it will greatly affect consumer purchasing decisions. The company also should improve the service quality in order to improve passenger comfort on the trip.